EVALUASI PENYALURAN ANGGARAN PENDAPATAN DAN BELANJA NEGARA ATAS DANA ALOKASI KHUSUS FISIK TAHUN 2017 (STUDI PADA KABUPATEN MAGELANG DAN BOYOLALI) - Suci Wulan Sari (ABIS: Accounting and Business Information Systems Journal, 2018)
ABSTRACTState budget (APBN) disbursement for physical special allocation fund of 2017 underwent a change compared with the disbursement in the previous year. The changes relate with requirements for disbursement and time limit for disbursement. Starting 2017, the physical special allocation fund disbursement is not only conducted at the State Treasury Office Jakarta II, but also at 171 state treasury offices all over Indonesia. This change requires the preparedness of state treasury offices and local governments in carrying out the disbursement of physical special allocation. In 2017, Boyolali regency government could disburse 98.22% of its physical special allocation fund, whereas Magelang regency government disbursed 67.61% of its physical special allocation fund. This research aims to evaluate the causes of non-optimal disbursement of physical special allocation fund at Magelang regency government based on the disbursement of physical special allocation fund at Boyolali regency government.This is a qualitative research with a case study approach. The evaluation process is conducted through benchmarking and analysis of the data from interviews with sources related with the disbursement of physical special allocation fund at Magelang and Boyolali regency governments, and from analysis of related documents. The research results show that there are two factors which caused the non-optimal disbursement of physical special allocation fund at Magelang regency, namely technical and non-technical factors. The technical factors include the tardy bidding time; types of activity which are too specific; and unmet output. The non-technical factors include lack of coordination; lack of local government’s roles; and thinking patterns shift.